Al-Naẓm Stylistic Discourse in I’jāz al-Qur’ān Based on Al-Jurjānī’s Perspective: Analysis of Arabic Literature Criticism on the Qur'an Studies - Ahmad Atabik (Universitas Islam Negeri Mataram, 2021)
This article discusses Arabic literature criticism during the classical period represented in al-Jurjāni’s naẓm (poetic) theory. It aims to analyze al-Jurjānī's thoughts in the field of balāgha (Arabic rhetoric) in revealing the miracles of the Qur'an in terms of its language beauty. Al-Jurjānī argues that one of the miraculous aspects of the Qur'an is concerned with its naẓm. Although the theory of naẓm had been previously proposed by Arabic literary scholars, such as al-Jāhiẓ, al-Baqillānī and al-Rummānī, al-Jurjānī, however, elaborated and developed the theory naẓm in great details. His theory contributes to the development of the meaning of balāgha and introduces it to public audience amongst scholars of the Qur’an. Al-Jurjānī concludes that naẓm is determined by the meaning of the Qur'anic verses as well as the structure in the discipline of naḥwu (grammar). The naḥwu and naẓm theory work together to generate meaning of the spoken sentence. Al-Jurjānī’s concept of naẓm supersedes later experts' and even modern Western linguists' discoveries and knowledge in the field of Arabic literary criticism.